DETERMINATION OF DRYING PARAMETERS OF JERUSALEM ARTICHOKE TUBERS - Слащева, Аліна (SWorldJournal, 2025)
A study was conducted on the dependence of the speed, duration, and kinetics of Jerusalem artichoke drying on air temperature. Rational parameters for drying Jerusalem artichoke tubers have been determined from the point of view of the maximum degree of p